Determination of inorganic arsenic species by Hydride Generation Atomic Absorption Spectrotometry with Cathodic Stripping Voltammetry - Tawatchai Kangkamano (2007)
Thesis (M.Sc., Analytical Chemistry)--Prince of Songkla University, 2007